GAS-IN-LIQUID FLOW DETECTOR USING ELECTRICAL CAPACITANCE TOMOGRAPHY{ECT) - Mustafa, Maisarah (Universiti Teknologi Petronas, 2011)
The multiphase flow characterization is a significant task for monitoring, measuring or controlling industrial processes especially in petroleum industry. The flow structures are classified in flow regimes, whose precise characteristics depend on a number of parameters which are velocity of gas and flow rate of the water. The various flow regimes are formed based on the distribution of the fluid phases in space and time differs. The objective of this study is to visualize the flow of gas in liquid phase which is capable in assisting operation which is flow regime identification. Electrical Capacitance Tomography (ECT) is a technique for obtaining information about the distribution of the contents of closed pipes or vessels by measuring variations in the dielectric properties of the material inside the vessel. 12-electrode ECT sensor is being used in order to capture the flow structure where the cross section is to be imaged fonned from simple metal plates. The basic principle of designing ECT sensor including the number of length of electrodes, earthed screen, stray capacitance effect and the connection issues must take into account. In this project, the author used inner pipe diameter of 2.1cm, outer pipe diameter is 2.5cm, electrode length of 5cm, electrode width of0.4cm and space between the electrodes is 0.3cm The online ECT sensor measures the voltage and capacitance for the varying flow regime. From the measurements, the permittivity image can be produced. In this project, the amount of the air flow is varying while the amount of water is constant. The author analyzed the results and compared with the physical observation. The reliability and verification of method is demonstrated by comparison of deionized water and normal water. By implementing this method, the visualization of the cross-sectional of the flow will be detem1ined and this method is important for industrial process monitoring.